FOMO (Fear Of Missing Out) - diagnostic and educational challenge - Łukasz Tomczyk (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The aim of the article is to characterize the phenomenon of FOMO in the diagnostic perspective. This special type of Internet addiction has been discussed in the context of the socio-educational challenge included in the paradigm of the risk media pedagogy. The FOMO phenomenon is a relatively new risky behavior that emerged due to the dissemination of new media. The text attempts to analyze FOMO taking into account various diagnostic criteria. The article is divided into two parts. The first one includes basic information about Internet addiction, and the second one is devoted to the FOMO measurement methods.